2020
DOI: 10.1186/s12911-020-1061-z
|View full text |Cite
|
Sign up to set email alerts
|

Advancing laboratory medicine in hospitals through health information exchange: a survey of specialist physicians in Canada

Abstract: Background: Laboratory testing occupies a prominent place in health care. Information technology systems have the potential to empower laboratory experts and to enhance the interpretation of test results in order to better support physicians in their quest for better and safer patient care. This study sought to develop a better understanding of which laboratory information exchange (LIE) systems and features specialist physicians are using in hospital settings to consult their patients' laboratory test results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Laboratory testing occupies a prominent place in healthcare. 20 While interoperability of laboratory data can improve patient care, 3 if it is not sufficiently complete, accurate, and comparable, then attempts at data exchange across institutions can result in potential patient safety issues. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Laboratory testing occupies a prominent place in healthcare. 20 While interoperability of laboratory data can improve patient care, 3 if it is not sufficiently complete, accurate, and comparable, then attempts at data exchange across institutions can result in potential patient safety issues. 21 …”
Section: Discussionmentioning
confidence: 99%
“…HIE has been shown to be a catalyst to encourage patients to be shared across multiple clinical sites; however, sharing of patient populations may lead to concerns of potential clinical competition between hospitals [54,88]. Functional HIE enables access to critical decision-driving data, such as laboratory findings and test results [89]. Acknowledging the breadth of hospital types and clinical catchment area demographics, studies have shown that the type of hospital can impact the quality of HIE [53,90].…”
Section: Hospitalsmentioning
confidence: 99%
“…Previous research has shown that dHealth has the potential to prevent disease 3,4 and lower healthcare costs, 5,6 while helping patients monitor and selfmanage chronic conditions 7,8 or optimizing the identification and use of available community resources by frail and isolated older adults. 9,10 It has also been shown that dHealth technologies can improve the quality, continuity, and availability of care, [11][12][13] tailor medical treatments for individual patients 14,15 and facilitate remote patient assessment and follow-up during pandemics. 16,17 For the practice of medicine to continue transforming itself and producing better outcomes for patients, future generations of physicians must be able to navigate with ease in an ever-changing digital environment.…”
Section: Introductionmentioning
confidence: 99%